An integrated pre-pregnancy care programme framework theoretically modelled from the perspectives of women with Type 2 diabetes and healthcare professionals. (December 2021) - Forde, Rita; Collin, Jacqueline; Brackenridge, Anna; Chamley, Mark; Hunt, Katharine; Forbes, Angus
Abstract: Background: Pregnancies in women with diabetes are associated with significant additional risks for the fetus, infant and mother such as, higher risk of stillbirths or congenital anomalies. Pre-pregnancy care can attenuate these risks. However, while women with Type 2 diabetes account for half of pregnancies in women with pre-existing diabetes, they are much less likely to receive pre-pregnancy care than women with Type 1 diabetes. This discrepancy may be related to the fact that most pre-pregnancy care is located in specialist diabetes centres where women with Type 1 diabetes are managed; whereas women with Type 2 diabetes are managed in primary care and reproductive care is not a routine element of diabetes care. Therefore, to improve pre-pregnancy care among women with Type 2 diabetes strategies need to be tailored to the specific needs of this group and the context of their diabetes care. Objectives: This paper seeks to inform the development of an integrated pre-pregnancy care programme by presenting strategies identified by women with Type 2 diabetes and healthcare professionals that address some of the barriers they experience in relation to pre-pregnancy care. Methods: A qualitative study using semi-structured in-depth interviews with women of reproductive age with Type 2 diabetes (n=30) and diabetes healthcare professionals (n=22) from both primary and secondary care. Data were transcribed verbatim and analysed thematically using Framework Analysis. The identified themes were then mapped to create a theoretical intervention framework using Normalisation Process Theory and the Capabilities, Opportunity, and Motivation to perform a Behaviour model. Results: Six themes were identified expressing the need for a multimodal approach for improving the uptake of pre-pregnancy care in women with Type 2 diabetes. These themes were then mapped onto the constructs of Normalisation Process Theory as follows: coherence (enhancing understanding of reproductive needs among women and healthcare professionals); cognitive participation (constructing a positive narrative for pregnancy and Type 2 diabetes); collective action (increasing the visibly of the reproductive needs of women, integrating healthcare systems and utilising supportive technologies); and reflexive monitoring (using multi-modal approaches to support systemised care). The data were also modelled to identify target behaviours for intervention detailing what needs to be done by whom, when and where. Conclusion: Women with Type 2 diabetes account for half of pregnancies in those with pre‐existing diabetes; however, they are less likely to receive pre‐pregnancy care than women with Type 1 diabetes. Pre-pregnancy care can reduce the maternal and fetal risks associated with Type 2 diabetes. This study presents strategies to improve the current low uptake of pre-pregnancy care for women with Type 2 diabetes. These strategies have been tailored to the specific needs of women and healthcare professionals and support integration within the woman's routine diabetes management.